From Tragedy To Opportunity: Hospital-based Violence Intervention Programs May Address Root-Cause Health Disparities for Violent Traumatic Injury Patients - Khadija Brouillette; Joseph Gebru; Armaan K Malhotra; Tyler McKechnie; Husain Shakil; Joseph Tropiano; Adom Bondzi-Simpson (Journal of Primary Care & Community Health)
Violence is a growing public health issue that disproportionately affects low-income and racialized communities across North America. While trauma centers appropriately respond to acute violent injuries, many patients are discharged back into the same environments that put them at risk. Hospital-based Violence Intervention Programs (HVIPs) offer opportunities for trauma care to address the upstream root causes of violence. These programs engage patients during critical “teachable moments,” connecting them to staff with lived experience, along with social workers and community partners, providing personalized support such as mental health care, education, employment, and housing services. In Canada, several initiatives in Toronto and Winnipeg are examples of HVIPs assisting with reduction of repeat injury by intervening on root causes. The early results show reductions in re-injury, improved engagement in school, lower justice system involvement, and potential healthcare cost savings. This commentary explores Canadian HVIPs as a model for addressing health disparities linked to violence and considers how similar approaches can be adapted in other healthcare settings to better serve communities.